Clinical features and isokinetic parameters in assessing injury risk in elite football players - Liporaci, R. F.; Saad, M.; Bevilaqua Grossi, D.; Riberto, M. (International Journal of Sports Medicine, 2019)
Football players frequently face the occurrence of non-contact injuries. Although there are likely multiple factors that contribute to increased risk of non-contact injury, it remains a challenge to correlate all these factors. However, it is not clear how much of individual training abilities may interfere in these events. As such, the primary aim of the present study was to determine whether the reduction of functional performance of the thigh in the isokinetic knee tests, anthropometric and morbid history can establish risk factors for lower-limb musculoskeletal injuries throughout the season. The incidence of injuries and odds ratios were calculated for suspected risk factors. Hamstring/Quadriceps conventional ratio outside of the safety range (55-64%) may be involved in the occurrence of non-contact muscle injuries and the risk for any musculoskeletal injuries in the lower extremities is 16 times higher when extensor peak of torque exceeds 10% and 12 times higher when flexor peak of torque difference was greater than 10%. This kind of evaluation can result in intervention programs that may decrease the risk of lower-limb musculoskeletal injuries. Based on these results we can establish a specific and individualized exercise program for each athlete and thus protect them during the season.